Performance analysis and optimization of heat exchangers: a new thermoeconomic approach - Sahin, Bahri; Ust, Yasin; Teke, Ismail; Erdem, Hasan Huseyin (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
A thermoeconomic performance optimization has been carried out for a single pass counter-flow heat exchanger model. In the considered model, the irreversibilities due to heat transfer between the hot and cold stream are taken into account and other irreversibilities such as pressure drops and flow imbalance are ignored. The objective function is defined as the actual heat transfer rate per unit total cost considering lost exergy and investment costs. The optimal performance and design parameters which maximize the objective function have been investigated. The effects of the technical and economical parameters on the general and optimal thermoeconomical performances have been also discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Thermoeconomics; Performance analysis; Optimization; Entropy generation; Counter-flow heat exchanger; Investment cost; DESIGN; PIPE; Thermodynamics; Energy & Fuels; Engineering; Mechanics